On the Feasibilities of Using the Wavelet Analysis of Mueller Matrix Images of Biological Crystals. (30th May 2010) - Dubolazov, O. V.; Ushenko, A. G.; Bachynsky, V. T.; Peresunko, A. P.; Vanchulyak, O. Ya.
Abstract : The efficiency of using the statistical and fractal analyses for distributions of wavelet coefficients for Mueller matrix images of biological crystal networks inherent to human tissues is theoretically grounded in this work. The authors found interrelations between statistical moments and power spectra for distributions of wavelet coefficients as well as orientation-phase changes in networks of biological crystals. Also determined are the criteria for statistical and fractal diagnostics of changes in the birefringent structure of biological crystal network, which corresponds to pathological changes in tissues.